Diagnostic Accuracy of Doppler Ultrasonography in Diagnosing Endometrial Carcinoma in Post-Menopausal Bleeding Females Taking Histopathology as Gold Standard (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the diagnostic accuracy of Doppler Ultrasonography in diagnosing endometrial carcinoma in females with post-menopausal bleeding taking histopathology as gold standard.Introduction: Postmenopausal bleeding (PMB) is one of the most common reasons in patients attending gynecological OPD. It is a frequent and alarming sign of endometrial cancer though the commonest cause is an atrophic endometrium. Women with PMB are categorized as those with spontaneous bleeding and those with bleeding whilst on Tamoxifen or HRT. All these patients should be investigated by TVS, hysteroscopy and D&C and accordingly should be managed.Methods:Study Design: Cross Sectional Study.Setting: Unit IV, Department of Obstetrics & Gynecology, Sir Ganga Ram Hospital, Lahore.Duration: Study was completed (01-07-13 to 30-12-14)Methodology: Total 250 cases were included in the study of age 50-70 years presented with clinically diagnosed postmenopausal bleeding (as per operational definition) undergoing hysterectomy. After approval from hospital ethical committee, 250 patients who fulfill the inclusion and exclusion criteria was enrolled in the study from OPD of Sir Ganga Ram Hospital, Lahore. Informed consent was obtained. All basic demographic information of each patient was obtained. Females were referred to radiology department for evaluation of endometrial thickness and RI value. If RI was to be
Keywords: Diagnostic accuracy, Doppler Ultrasonography, Endometrial carcinoma, Post-menopausal bleeding, Histopathology.